Best practices in teaching digital literacies - Ortlieb, Evan; Cheek, Earl H.; Semingson, Peggy, 1973- (Literacy research, practice and evaluation, 2018)
This edited volume provides a practical framework for teacher education programs to develop K-12 students' digital literacies. It serves as a set of best practices in teaching digital literacies that promotes access to research-based pedagogies for immediate implementation in their classrooms.